2019
DOI: 10.1093/milmed/usz046
|View full text |Cite
|
Sign up to set email alerts
|

Extended Ketogenic Diet and Physical Training Intervention in Military Personnel

Abstract: Introduction Ketogenic diets (KDs) that elevate ketones into a range referred to as nutritional ketosis represent a possible nutrition approach to address the emerging physical readiness and obesity challenge in the military. An emerging body of evidence demonstrates broad-spectrum health benefits attributed to being in nutritional ketosis, but no studies have specifically explored the use of a KD in a military population using daily ketone monitoring to personalize the diet prescription. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 43 publications
4
60
0
Order By: Relevance
“…Kephart et al also found no negative results on the 1RM back squat when compared to a NKD group. Recently, it has been reported similar changes on anaerobic parameters related to lower and upper-limb strength and power between a KD and NKD groups [42]. In fact, our study also showed similar increases on power (CMJ) after the dietary interventions in both groups from baseline.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Kephart et al also found no negative results on the 1RM back squat when compared to a NKD group. Recently, it has been reported similar changes on anaerobic parameters related to lower and upper-limb strength and power between a KD and NKD groups [42]. In fact, our study also showed similar increases on power (CMJ) after the dietary interventions in both groups from baseline.…”
Section: Discussionsupporting
confidence: 85%
“…The nutritional intervention of this study did not consider specific values of total calories or macronutrients used per g•kg − 1 •d − 1 , impairing the ability to estimate whether participants were in a state of energy deficiency or surplus. Similarly, recent research on male military personnel have shown a reduction on BM (including FFM loss) in the KD group only, while the NKD group increased this parameter with a significant reduction in FM; notwithstanding, energy intake was not controlled in this study [42]. In contrast, Volek et al [43] reported a statistically significant increase in FFM (1.1 kg) in moderately active male participants, some of whom reported routinely performing moderate intensity RT, following a 6-week RT program.…”
Section: Discussionmentioning
confidence: 46%
“…Nonetheless, individuals with T1D often make claims in various social media forums and in some self-report surveys (see below) that they can still be physically active and train while adhering to a LCD. Interestingly, LaFountain and colleagues [39] found that a 12-week VLCD (≤50 g carbohydrate per day) did not compromise physical performance compared to a mixed diet in military personnel without T1D. The study also demonstrated improved insulin sensitivity and body composition following the VLCD alongside high adherence.…”
Section: Defining Low Carbohydrate Dietsmentioning
confidence: 97%
“…69 Endogenous and exogenous ketones have been demonstrated to reduce acute and/or chronic markers of glycemic load in healthy and diabetic populations. 41,49,[70][71][72][73] We hypothesize that consumption of exogenous ketones may improve specific clinical outcomes of respiratory viral infection through already-understood molecular mechanisms. Older patients and patients with diabetes, in whom these mechanisms are most relevant, may be the groups most likely to benefit from exogenous ketone body administration.…”
Section: Introductionmentioning
confidence: 99%
“…69 Endogenous and exogenous ketones have been demonstrated to reduce acute and/or chronic markers of glycemic load in healthy and diabetic populations. 41 , 49 , 70 , 71 , 72 , 73 …”
Section: Introductionmentioning
confidence: 99%